Augmented Reality and the Metaverse - Speculating about the Future - Shahper Richter; Nastaran Mohammadhossein; Alexander Richter; Matthias Trier (Australasian Journal of Information Systems, 2025)
Imagine a world where the boundaries between physical and digital realities dissolve, creating immersive experiences that transform how we interact. This potential lies at the heart of the Metaverse, and a confluence of technologies such as AR, VR, AI and blockchain will be the key to unlocking it. We employ a novel combination of horizon scanning and narrative development to explore the transformative role of AR within the Metaverse. This approach reveals potential technology-driven futures, highlighting emerging trends and disruptions not readily apparent through traditional forecasting methods. Our narratives of the future offer surprising glimpses into potential sociotechnical futures, informing a research agenda for both industry and academia.